2012
DOI: 10.1177/0886260511432152
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in Police-Reported Intimate Partner Violence Perpetration

Abstract: The objectives of this study were to examine racial and ethnic disparities in perpetrator and incident characteristics and discrepancies between police charges and reported perpetrator behaviors in police-reported intimate partner violence (IPV). This cross-sectional study used standardized police data and victim narratives of IPV incidents reported to the police in Dallas, Texas in 2004. The sample included non-Hispanic White, non-Hispanic Black, and Hispanic male perpetrators who were residents of Dallas (N … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 40 publications
2
21
2
Order By: Relevance
“…Previous studies have shown differences by age (Brown et al, 2013a; Schussler-Fiorenza Rose et al, 2014; Centers for Disease Control and Prevention (CDC) and 2009), gender (Kelly-Irving et al, 2013; Liu et al, 2013; Roxburgh and Macarthur, 2014), race/ethnicity (Brown et al, 2013a; Schussler-Fiorenza Rose et al, 2014; Centers for Disease Control and Prevention (CDC) and 2009; Roxburgh and Macarthur, 2014), income (Brown et al, 2013a; Schussler-Fiorenza Rose et al, 2014), education (Schussler-Fiorenza Rose et al, 2014; Centers for Disease Control and Prevention (CDC) and 2009), marital status (Brown et al, 2013a; Schussler-Fiorenza Rose et al, 2014), and insurance status (Brown et al, 2013a), associated with ACEs. Statistically significant differences by age (Brown et al, 2013b; Palmetto et al, 2013), sex (Clark et al, 2014; Cui et al, 2013; Lovestad and Krantz, 2012; Menard et al, 2014), race/ethnicity (Palmetto et al, 2013; Clark et al, 2014; Lipsky et al, 2012; Stephenson et al, 2011), income (Brown et al, 2013b; Edwards et al, 2014), education (Brown et al, 2013b; Stephenson et al, 2011), marital status (Brown et al, 2013b; Cui et al, 2013), and insurance status (Brown et al, 2013b) were associated with IPV. Therefore, the proposed study controlled for the following sociodemographic characteristics as confounders namely: age, race/ethnicity, income, education, marital status and insurance status.…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies have shown differences by age (Brown et al, 2013a; Schussler-Fiorenza Rose et al, 2014; Centers for Disease Control and Prevention (CDC) and 2009), gender (Kelly-Irving et al, 2013; Liu et al, 2013; Roxburgh and Macarthur, 2014), race/ethnicity (Brown et al, 2013a; Schussler-Fiorenza Rose et al, 2014; Centers for Disease Control and Prevention (CDC) and 2009; Roxburgh and Macarthur, 2014), income (Brown et al, 2013a; Schussler-Fiorenza Rose et al, 2014), education (Schussler-Fiorenza Rose et al, 2014; Centers for Disease Control and Prevention (CDC) and 2009), marital status (Brown et al, 2013a; Schussler-Fiorenza Rose et al, 2014), and insurance status (Brown et al, 2013a), associated with ACEs. Statistically significant differences by age (Brown et al, 2013b; Palmetto et al, 2013), sex (Clark et al, 2014; Cui et al, 2013; Lovestad and Krantz, 2012; Menard et al, 2014), race/ethnicity (Palmetto et al, 2013; Clark et al, 2014; Lipsky et al, 2012; Stephenson et al, 2011), income (Brown et al, 2013b; Edwards et al, 2014), education (Brown et al, 2013b; Stephenson et al, 2011), marital status (Brown et al, 2013b; Cui et al, 2013), and insurance status (Brown et al, 2013b) were associated with IPV. Therefore, the proposed study controlled for the following sociodemographic characteristics as confounders namely: age, race/ethnicity, income, education, marital status and insurance status.…”
Section: Methodsmentioning
confidence: 99%
“…9 Marital status was found to be associated with incident characteristics of IPV. 33 HIV testing differs by race/ethnicity, with black and Hispanic women being less likely than white women to be tested. 34 Colorectal cancer screening varies by race/ethnicity.…”
Section: Methodsmentioning
confidence: 99%
“…Despite research showing that minority and low-income communities often have both higher rates of IPV [22, 23] and fewer IPV-related resources [21], these topics remain disconnected in the literature. To the best of our knowledge, no previous studies have evaluated the availability of IPV-related healthcare services relative to IPV arrests as a means for evaluating the extent of spatial concordance between IPV-related need and resources, and what factors are associated with any observed spatial mismatch.…”
Section: Introductionmentioning
confidence: 99%